The Efficacy of Radiofrequency Turbinate Reduction in Hypertrophied Inferior Turbinate - Omkaltoum Shafter, (AlQalam Journal of Medical and Applied Sciences, 2025)
Inferior turbinate hypertrophy (ITH) is a predominant etiology of chronic nasal obstruction, often refractory to medical management with corticosteroids and antihistamines. When medical therapy fails, surgical intervention is indicated to reduce turbinate volume and restore nasal patency. Radiofrequency turbinate reduction (RFTR) has emerged as a minimally invasive technique that utilizes submucosal thermal energy to induce controlled volumetric tissue reduction with minimal morbidity. This study was conducted to evaluate the subjective efficacy and temporal profile of RFTR in the management of bilateral ITH refractory to medical therapy. A retrospective study, this investigation included 50 patients with persistent nasal obstruction due to bilateral ITH. All participants underwent a single session of bilateral RFTR. Subjective symptom severity was assessed using a Visual Analog Scale (VAS) for nasal obstruction preoperatively and at postoperative intervals of 1 week, 1 month, 3 months, and 6 months. Statistical analysis was performed to compare the pre- and postoperative scores. Forty-seven patients completed the follow-up protocol. A statistically significant reduction in VAS scores for nasal obstruction was observed at all postoperative time points compared to preoperative baselines (p < 0.05). Symptomatic improvement commenced at the first postoperative week and was sustained through the 3-month assessment. While a minor recrudescence in symptoms was noted at the 6-month follow-up, the mean VAS score remained significantly improved over the preoperative value (p < 0.05). Overall, 89.4% of patients reported satisfactory symptomatic improvement over the 6-month study period. Radiofrequency turbinate reduction is an effective and safe intervention for providing significant and sustained subjective relief of nasal obstruction in patients with medically refractory inferior turbinate hypertrophy.